Evidence of disturbed sleep and mood state in well-trained athletes during short-term intensified training with and without a high carbohydrate nutritional intervention. Issue 14 (18th July 2017) - Killer, S. C.; Svendsen, I. S.; Jeukendrup, A. E.; Gleeson, M.
ABSTRACT: Few studies have investigated the effects of exercise training on sleep physiology in well-trained athletes. We investigated changes in sleep markers, mood state and exercise performance in well-trained cyclists undergoing short-term intensified training and carbohydrate nutritional intervention. Thirteen highly-trained male cyclists (age: 25 ± 6y, O2max : 72 ± 5 ml/kg/min) participated in two 9-day periods of intensified training while undergoing a high (HCHO) or moderate (CON) carbohydrate nutritional intervention before, during and after training sessions. Sleep was measured each night via wristwatch actigraphy. Mood state questionnaires were completed daily. Performance was assessed with maximal oxygen uptake ( . Percentage sleep time fell during intensified training (87.9 ± 1.5 to 82.5 ± 2.3%; p < 0.05) despite an increase in time in bed (456 ± 50 to 509 ± 48 min; p = 0.02). Sleep efficiency decreased during intensified training (83.1 ± 5.3 to 77.8 ± 8.6%; p < 0.05). Actual sleep time was significantly higher in CON than HCHO throughout intensified training. Mood disturbance increased during intensified training and was higher in CON than HCHO (p < 0.05). Performance in the exercise protocol fell significantly with intensified training. The main findings of this study were that 9-days of intensified training in highly-trained cyclists resulted in significant and progressive declines in sleep quality, mood state and maximal exercise performance.